Blue and green infrastructure proposal for an urban watershed in São Paulo to peak flow reduction - Alencar, Juliana de; Rizzi, Daniela; Pereira, Lívea; Vasconcelos, Ivna Gadelha Diógenes; Peduto, Thais Goya; Trindade, Lessandro Morini; Becker, Vanessa Constansa; Souza, Murillo Henrique de; Madureira, Ronaldo Gonçalves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The critical issue of floods in Brazilian cities is a consequence of an accelerated and disordered occupation and urbanization process, which results in excessive soil waterproofing, removal of riparian vegetation, silting of rivers and streams, water pollution, among others. In the last decades, the use of conventional drainage techniques has resulted in many problems, due to the fast flow of water to downstream and the pollutant loads that flow to the watercourses. Through Green Infrastructure it is possible to promote urban rainwater storage and infiltration, reducing the probability of flooding, and allowing for the retention of pollutants and consequent improvement of water quality in urban water systems. In this study, the application of Blue-Green Infrastructure (BGI) techniques for the reduction of peak flow and improve the water quality are proposed for the Jacarezinho watershed, located in the Municipality of São Paulo. Hydrological simulations of the proposed solutions indicated a reduction of about 36% of the peak flow, which highlights the relevance of BGI. Unlike the Brazilian conventional drainage that practice the construction of monofunctional flood storage reservoirs (called in Brazil as “piscinões”), the BGI also promotes a harmonious and balanced interaction between the population and the urban landscape.